Humanizing teaching pedagogy : an evaluation of disciplinary literacy in higher education - Khetoa, Soyiso Godsave; Mokala, Ntsoaki Teresa; Matee, Lihotetso Gloria (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
Studies have suggested that there is a discerning literacy challenge in South Africa. The literacy crisis in South Africa is not unique to higher education institutions. The current study focuses on humanising teaching pedagogy at institutions of higher education. In this study, more focus is placed on the evaluation of disciplinary literacy in higher education. This is a mixed method research premised on an interpretivist paradigm. The study uses secondary data from one of the authors' Phd study conducted in one institution of higher learning in South Africa. Data was collected through questionnaires and interviews. The study purposely selected second- and third-year students enrolled in Sesotho module, either as a major or as an elective in one university in South Africa. Ethical clearance was obtained from the university where data was collected. Findings of the study point to students believing that the incorporation of their primary languages can have benefits towards their education. Students also indicated that most of them struggle to participate fully in lectures due to their limitations in English command. Our recommendation is that diverse repertoires must be viewed as resources upon which students can rely on to empower themselves in humanising education provision. The study further recommends that multilingual pedagogies such as translanguaging can be useful to advance the project of teaching and learning in higher education and provide opportunities for self-reflections
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 7 (1) (2023)
Keywords: Decolonization; Academic literacy; Translanguaging; Transformation; Home language teaching.; Literacy -- South Africa; Education -- Study and teaching; Teaching -- South Africa; Education, Higher -- South Africa